Cardioprotective Effect of Ulmus wallichiana Planchon in β-Adrenergic Agonist Induced Cardiac Hypertrophy - Syed, Anees A.; Lahiri, Shibani; Mohan, Divya; Valicherla, Guru R.; Gupta, Anand P.; Kumar, Sudhir; Maurya, Rakesh; Bora, Himanshu K.; Hanif, Kashif; Gayen, Jiaur R. (Frontiers in Pharmacology, 2016)
Ulmus wallichiana Planchon (Family: Ulmaceae), a traditional medicinal plant, was used in fracture healing in the folk tradition of Uttarakhand, Himalaya, India. The present study investigated the cardioprotective effect of ethanolic extract (EE) and butanolic fraction (BF) of U. wallichiana in isoprenaline (ISO) induced cardiac hypertrophy in Wistar rats. Cardiac hypertrophy was induced by ISO (5 mg/kg/day, subcutaneously) in rats. Treatment was performed by oral administration of EE and BF of U. wallichiana (500 mg/kg/day and 50 mg/kg/day). The blood pressure (BP) and heart rate (HR) were measured by non-invasive blood pressure (NIBP) measurement technique. Plasma renin, Ang II, NO and cGMP level were estimated using an ELISA kit. ACE activity was estimated. Blood pressure and heart rate were significantly increased in ISO group (130.33± 1.67 mmHg vs 111.78±1.62 mmHg, p<0.001 and 450.51±4.90 beats/min vs 347.82±6.91 beats/min respectively, p<0.001). The BP and HR were significantly reduced (EE: 117.53±2.27 mmHg vs 130.33±1.67 mmHg, p<0.001, BF: 119.74±3.32 mmHg vs 130.33±1.67 mmHg, p<0.001); HR: (EE: 390.22±8.24 beats/min vs 450.51±4.90 beats/min, p<0.001, BF: 345.38±6.79 beats/min vs 450.51±4.90 beats/min, p<0.001) after the treatment of EE and BF of U. wallichiana, respectively. Plasma renin, Ang II, ACE activity was decreased and NO, cGMP level were increased. The EE and BF of U. wallichiana down regulated the expression of ANP, BNP, TNF-α, IL-6, MMP9, β1 AR,TGFβ1 and up regulated NOS3, ACE2 and Mas expression level respectively. Thus, this study demonstrated that U. wallichiana has cardioprotective effect against ISO induced cardiac hypertrophy.